تحليل ذاتية الشخصية الرئيسية في رواية نارنجة لجوخة الحارثي: التحليل النفس لكارل غوستاف يونغ - salsabila salsabila (EL- Hayah, 2024)
This research is motivated by data from the novel Narinjakh by Jokha Al-Harithi which shows the results of the personality type possessed by the main character Bunga. The theory used in this research is Carl Gustav Jung's psychoanalytic theory which focuses on subjective personality types. This research aims to describe and analyze the personality type of the main character Zohour. These include Introverted Thinking, Introverted Feeling, Introverted Sensing, Introverted Intuitive, Extraverted Thinking, Extraverted Feeling, Extraverted Sensing, and Extraverted Intuitive. The type of research used is descriptive qualitative, with primary data in the form of quotations that explain the subjectivity of the main character and the source is the novel Naranja. The data collection method uses library techniques, namely data collection techniques by searching documents, and at the same time analyzing the data using reduction, description and inference. The results of the research carried out were the main factors causing the formation of the main character's subjectivity which were found through 6 indicators in the form of self-awareness which were analyzed based on a review of Carl Gustav Jung's psychoanalytic personality theory, namely the form of emotion, regret and deep feelings of guilt felt by the main character towards his grandmother who abandoned him.